Feminism and the politics of resilience : essays on gender, media and the end of welfare - McRobbie, Angela (Medford, MA : Polity, 2020)
'A captivating analysis of neoliberal culture's hold on womanhood from the leading voice in cultural studies'--
Includes bibliographical references:(pages 125-140) and index.
Keywords: Feminism; Neoliberalism; Popular culture -- Political aspects